Pengelolaan Kenaikkan Pangkat Guru Pegawai Negeri Sipil Dengan Menggunakan Sistem Informasi Manajemen Kepegawaian Di Mts Qaryatul Jihad Bengkulu Tengah - Tantriana , Mira (Manajer Pendididikan, 2024)
The purpose of the study was to describe the management of teacher promotion using the personnel management information system at MTs Qaryatul Jihad Central Bengkulu. This study used qualitative descriptive method. Data collection techniques use observation, documentation, and interviews. Data analysis techniques consist of data collection, data reduction, data presentation, and conclusions. The subject of this study was MTs teacher Qaryatul Jihad Central Bengkulu. The results showed that planning was carried out to form a special work team known as the Teacher Performance Assessment and Continuous Professional Development team, for implementation carried out on a scheduled and programmatic basis, the results of evaluations were carried out annually by all teachers to measure the success of the program made, and the inhibiting factor in the management process was still the lack of teacher ability in technology, these obstacles can be overcome by following Online or offline training.